Osteopenia and osteoporosis among treatment-experienced people living with HIV - Lara,Bárbara Marques de Castro (2020)
Abstract Introduction Life expectancy of people living with human immunodeficiency (PLHIV) has increased mainly due to the accessibility and effectiveness of antiretroviral therapy (ART). However, adverse effects from long-term use of antiretrovirals, and the physiological changes associated with aging, may compromise the quality of life of PLHIV, in addition to causing new demands on the healthcare system. Objectives Estimate the frequency of osteoporosis and osteopenia in patients on prolonged ART and to verify their associated factors. Methods A cross-sectional study was conducted in Belo Horizonte, Minas Gerais, Brazil, from August 2017 to June 2018, in a sample of PLHIV (age≥18 years) who started ART between 2001 and 2005. Data were collected through face-to-face interviews, physical evaluation, laboratory tests, and Dual-Energy X-Ray Absorptiometry Screening (DEXA). The outcome of interest was presence of bone alteration, defined as presence of osteopenia or osteoporosis in DEXA. The association between the explanatory variables and the event was assessed through odds ratio (OR) estimate, with 95% confidence interval (CI). Multiple logistic regression was performed to evaluate factors independently associated with bone alteration. Results Among 92 participants, 47.8% presented bone alteration (19.6% osteoporosis and 28.2% osteopenia). The variables that remained in the final logistic regression model were age ≥ 50 years (OR: 12.53; 95% CI: 4.37–35.90) and current alcohol use (OR: 2.63; 95% CI: 0.94–7.37). Conclusions This study showed a high frequency of bone changes, especially in PLHIV older than 50 years. This information is useful to stimulate the screening and timely intervention of this comorbidity of PLHIV on prolonged use of ART in order to prevent or minimize complications and new demands on the healthcare system.